2007
DOI: 10.1158/1078-0432.ccr-06-2704
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human Papillomavirus Type 16 Oncoproteins Enhances Hypoxia-Inducible Factor 1α Protein Accumulation and Vascular Endothelial Growth Factor Expression in Human Cervical Carcinoma Cells

Abstract: Purpose: Human papillomavirus (HPV)-16 oncoproteins, E6 and E7, are associated with enhanced tumor angiogenesis in human cervical cancers. The purpose of this study was (a) to investigate whether expression of HPV-16 E6 and E7 oncoproteins induces hypoxia-inducible factor 1a (HIF-1a) and vascular endothelial growth factor expression in cervical cancer cells; and (b) to assess the effect of resveratrol on 16 E6-and E7-induced HIF-1a and VEGF gene expression. Experimental Design: Human cervical cancer cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 48 publications
8
95
2
1
Order By: Relevance
“…A few studies have shown that HPV E6/E7 could regulate VEGF expression. [36][37][38] However, the current result indicates that VEGF may also modulate HPV E7 expression.…”
Section: Short-lived Rnai In Hela Cellscontrasting
confidence: 51%
“…A few studies have shown that HPV E6/E7 could regulate VEGF expression. [36][37][38] However, the current result indicates that VEGF may also modulate HPV E7 expression.…”
Section: Short-lived Rnai In Hela Cellscontrasting
confidence: 51%
“…1). The tumor suppressor p53 is one of the most wellcharacterized target genes of HPV-16 E6 (8,30,31) besides the PDZ domain containing proteins (25), human telomerase reverse transcriptase (hTERT) (32), vascular endothelial growth factor (VEGF) (33,34), and hypoxia-inducible factor 1· (HIF-1· ) (34). p53 was recently reported to repress the DNMT1 level in human colon carcinoma HCT116 cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-induced HIF 1α stabilization, as VHL loss, could cooperate in organizing host defenses and have cellular consequences that in some cases can inhibit viral replication (49,50). However, in other instances of persistent viral infection, HIF-1 activation can lead to the activation of the proangiogenic program and oncogenic transformation as a consequence (11,(51)(52)(53)(54). Therefore, considering the primary role of HIF 1α in immune defense, it is not surprising that cells have evolved auxillary mechanisms to rapidly sustain the stabilization of HIF 1α, for instance through the degradation of VHL protein.…”
Section: E G F P P E G F P -S O C S 1 B O X P E G F P -S O C S 3 B O mentioning
confidence: 99%